COMPARATIVE STUDY OF MOLAR ABSORTIVITY USING VANADIUM- AZOLE ADDUCTS AND ITS SALT (Journal of Medical & Health Sciences Review, 2025)
The present study aimed to synthesize vanadium-bisbenzimidazolium adduct to compare its molar absorptivity with its respective salt. The coupler, bisbenzimidazolium salt, is a type of azolium salt which has potential to bind with vanadium ion to produce these adducts. UV-visible spectroscopic monitoring was used to characterize all the synthesized adducts. The structural properties and distinctions between these new adducts were compared to previously reported nitrogen-based adducts. Based on preliminary experiments, suitable ranges for experimental variables like coupling time, coupling temperature, and coupler concentration were determined for each synthesized adduct. Response Surface Methodology (RSM) with a quadratic design was then employed to plan and optimize the experiments using Design Expert 13.0. Analysis of Variance (ANOVA) was used to assess the significance of the experimental variables and their interactions. The results indicated that among the examined factors, coupler concentration had the most substantial impact on changing the spectroscopic characteristics of synthesized adduct.